SINERGITAS PEMERINTAH DAERAH DALAM MELAKSANAKAN PROGRAM PENGEMBANGAN SAGU BERKELANJUTAN DI KABUPATEN KEPULAUAN MERANTI - Susi Susanti; Khairul Anwar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The sago potentials in Meranti Islands Regency has not been used as a local food resource for the community had been so low compared to rice food. This study aimed to determine the synergy of Regional Governments in Implementing Sustainable Sago Development Program in Meranti Island Districts in 2015-2017. This study used a qualitative research. Data collection technique were interviews and documentation. Data analysis was limited to data processing techniques or facts obtained by developing categories that were relevant to the purpose of research and interpretation by referringto appropriate theories. The results of this study indicated that in the implementation of the sago bro program through the food security service and related agencies in its implementation it had not been in accordance with the stated objectives. This was because the government had not optimized socialization of the program regarding the program so that people consumed local food, namely sago, so that many people did not know about this program. Other than that it was caused by the resources that were implemented and the habits of the people who were not used to consuming sago as staple food for daily living in Kepulauan Meranti Regency. So related to the implementation of the program through diversification of sago consumption and empowerment of IKM, it can be concluded that the local government is not serious in implementing this sago development program because it has not produced a policy so that synergy between government agencies in the Meranti archipelago district has not been established optimally. Keywords : Synergy of Regional Government, Development of Sago